Analysis of Turnover and Retention in Early Childhood Education Teachers - Minarsih, Reni Windi; Madyawati, Lilis; Laely, Khusnul (ETDC: Indonesian Journal of Research and Educational Review, 2025)
High turnover of early childhood education teachers is a challenge to the quality of education. This situation compels leaders to focus on retaining teachers to ensure the sustainability of early childhood education institutions. This study aims to determine the factors that influence the turnover and retention rates of early childhood education teachers in the Magelang Region. This study uses a quantitative descriptive method through a survey approach. Data were collected through questionnaires distributed to early childhood education respondents in the Magelang Region using a simple random sampling technique. This study was analyzed using descriptive analysis, namely analyzing the average, number, and percentage. The results of the study indicate that the factors that influence the rate of teacher turnover are the work environment, suitability to work, culture, and community; compensation and benefits; leadership; work management system; and mentoring and support from colleagues. These findings suggest that school policies should focus on specific factors in the teachers' work environment by creating a fun, calming, and prosperous atmosphere to help reduce the impact of high teacher turnover and improve retention in early childhood education.